2019
DOI: 10.7150/ijbs.39063
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Colony-stimulating Factor Mediates the Recruitment of Macrophages in Triple negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC) is characterized by aggressive malignant tumor, poor prognosis and lack of targeted treatment. Several studies have established that macrophages are closely associated with the progression of TNBC. Through immunohistochemical analysis, we found that the infiltration of macrophage in TNBC tissue was more than that in non-triple negative breast cancer (nTNBC) tissue. Furthermore, the conditioned medium (CM) of MDA-MB-231 and HCC1937, the TNBC cell lines, had significant migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Re-emergence of expression of M-CSF and its receptor in breast tissue also occurs during breast tumorigenesis, a scenario that is associated with immunosuppression and aggressive disease. Malignancies of the breast that fall into this category include primary breast cancer with nodal involvement ( 21 24 ), post-menopausal breast cancer ( 25 ), and triple-negative breast cancer ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Re-emergence of expression of M-CSF and its receptor in breast tissue also occurs during breast tumorigenesis, a scenario that is associated with immunosuppression and aggressive disease. Malignancies of the breast that fall into this category include primary breast cancer with nodal involvement ( 21 24 ), post-menopausal breast cancer ( 25 ), and triple-negative breast cancer ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis-and inflammation-associated microenvironmental factor S100A4 activates the basal-like subtype of breast cancer cells to trigger monocyte-to-macrophage (M2) differentiation and polarization, and elevates secretion of pro-inflammatory cytokines such as IL-8, IL-6, CXCL10, CCL2 and CCL5 [67]. Further, macrophage colony-stimulating factor (M-CSF), the main stimulator of macrophage migration, caused aggregation of M2 macrophages through an increased elongation of pseudopodia [68]. Inhibitors of differentiation (ID) 4 significantly associates with M2 macrophage marker CD68 protein expression in a series of TNBC tissues.…”
Section: M2 Macrophagesmentioning
confidence: 99%
“…Of these growth factors, TNF-α, IL-8, TGF-β, M-CSF, and VEGF can have a direct effect on OC differentiation but not on OC activity (Wang et al, 2020). Of note, MDA-MB-231 cells that in our study showed the greatest effect are known to secrete very high levels of M-CSF, also higher than MCF7 cells (Lu et al, 2019). We also found that among the carcinoma cell lines examined, Caki-1 cells can directly and strongly promote OC activity, whereas MCF7 showed a very low, although significant effect, and MDA-MB-231 cells were not able to directly induce OC-mediated collagen type I degradation.…”
Section: Discussionmentioning
confidence: 50%